1984
DOI: 10.1139/b84-009
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development at cold-hardening temperatures. Chloroplast ultrastructure, pigment content, and composition

Abstract: Chloroplast ultrastructure, pigment content, and composition were investigated during growth of 'Puma' rye at warm and cold-hardening temperatures. Cytological characteristics of leaf mesophyll cells were altered upon growth at cold-hardening temperatures as indicated by an apparent increase in the amount of cytoplasm. Univacuolate and multivacuolate mesophyll cells were found in leaves from cold-hardened plants, but only univacuolate mesophyll cells were found in leaves from warm-grown plants. Chloroplast ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
39
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 0 publications
6
39
0
Order By: Relevance
“…(13) concluded that growth and development of winter rye at low temperature results in an alteration in protein-protein interactions associated with LHCII. This is consistent with previous reports which indicated that RH thylakoids exhibited a decrease in particle size on the EF fracture face ( 17), an increase in the F685/F742 but did not exhibit a concomitant increase in PSII activity at the expense of PSI activity nor any detectable change in photosynthetic unit size (11,(15)(16)(17). However, Huner et al (10,17) have also reported that no significant differences between RH and RNH thylakoids exist with respect to pigment or polypeptide composition.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…(13) concluded that growth and development of winter rye at low temperature results in an alteration in protein-protein interactions associated with LHCII. This is consistent with previous reports which indicated that RH thylakoids exhibited a decrease in particle size on the EF fracture face ( 17), an increase in the F685/F742 but did not exhibit a concomitant increase in PSII activity at the expense of PSI activity nor any detectable change in photosynthetic unit size (11,(15)(16)(17). However, Huner et al (10,17) have also reported that no significant differences between RH and RNH thylakoids exist with respect to pigment or polypeptide composition.…”
supporting
confidence: 91%
“…This is consistent with previous reports which indicated that RH thylakoids exhibited a decrease in particle size on the EF fracture face ( 17), an increase in the F685/F742 but did not exhibit a concomitant increase in PSII activity at the expense of PSI activity nor any detectable change in photosynthetic unit size (11,(15)(16)(17). However, Huner et al (10,17) have also reported that no significant differences between RH and RNH thylakoids exist with respect to pigment or polypeptide composition. In this report, we examine the lipid and fatty acid compositions of RH and RNH thylakoids in order to determine if the observed changes in the structure and function of RH LHCII are related to alterations in thylakoid lipid composition and content.…”
supporting
confidence: 91%
“…It was concluded that low growth temperature modulates the assembly and supramolecular organization of rye LHCII by altering specifically the trans-16:1 content of PG. The in vitro evidence for a low temperature induced change in the organization of LHCII is supported by in situ evidence such as freeze fracture (8), 77°K fluorescence emission spectra (5, 10) as well as evidence indicating a low temperature induced decrease in the extent ofthylakoid stacking (8,10).…”
mentioning
confidence: 85%
“…Tremolieres et al (9,24) were the first to present evidence that the trans-16:1 content of the primary phospholipid of higher plant thylakoids, PG, is correlated with the stabilization of the oligomeric form of LHCIIb. Subsequently, Huner et al (14,16) (12,14). Furthermore, PG has been shown to be tightly and specifically associated with LHCII during purification (16).…”
mentioning
confidence: 99%